BODY COMPOSITION AND PHYSICAL FITNESS RELATED TO THE HEALTH OF SCHOOL CHILDREN FROM 14 TO 18 YEARS OF A PARTICULAR SCHOOL OF THE CITY OF MANAUS (Fiep Bulletin - online, 2019)
Based on the objective of the study and according to the data obtained it is concluded that the level of AFRS inschoolchildren in a private school in Manaus is below internationally accepted levels of health, presenting risks of diseasesindependent of gender or age.The practice of physical activity should be encouraged by Physical Education professionals for a better developmentof motor skills related to health.Other researches in the region are emphasized regarding interventions, eating habits. To better understand thereasons that interfere with the results found.We also understand that with the permanent investigation of growth and physical fitness, we will have support forevaluation of motor skills, indicating the level of health of children and adolescents.